2005
DOI: 10.1016/j.rmed.2004.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation and oxidative stress in exacerbated chronic obstructive pulmonary disease patients

Abstract: COPD is characterised by damage to small airways due to an inflammatory process as well as an imbalance between oxidants and antioxidants. Several cytokines and cell adhesion molecules enhancing a mainly neutrophilic inflammation have been associated with COPD. The aim of the study was to investigate whether inflammation or oxidative markers gave an indication of the course of COPD during an exacerbation. Fourteen patients with moderate to severe COPD admitted to the St. Antonius Hospital because of an exacerb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 22 publications
3
62
0
9
Order By: Relevance
“…26,33,34 In COPD presence of endothelial dysfunction was also demonstrated. 35 Therefore, endothelial dysfunction might represent another link between COPD and SCF, whether it was initiated by smoking, inflammation or COPD itself.…”
Section: Discussionmentioning
confidence: 99%
“…26,33,34 In COPD presence of endothelial dysfunction was also demonstrated. 35 Therefore, endothelial dysfunction might represent another link between COPD and SCF, whether it was initiated by smoking, inflammation or COPD itself.…”
Section: Discussionmentioning
confidence: 99%
“…While no formal safety studies have been performed in COPD patients, there have been no adverse effects reported in studies in which EBC has been successfully collected from patients with unstable and severe COPD [13,14]. Transmission of infection between subjects using nondisposable EBC collection systems is theoretically possible, although bacterial DNA cross-contamination was not observed in a study of EBC taken from patients with cystic fibrosis (CF) [15].…”
Section: Ebc Collection Collection Devicementioning
confidence: 99%
“…It is easy to perform, relatively inexpensive and studies have reported good intra-assay reproducibility [14,43]. However, despite the use of identical ELISA kits in similar patient groups, the levels of biomarkers quoted between different studies have varied considerably.…”
Section: Gas Standardisationmentioning
confidence: 99%
“…Obrambeni mehanizmi organizma uklju~uju enzime za inaktivaciju peroksida i brojne spojeve za hvatanje slobodnih radikala (4). Oksidativni stres, prouzro~en neravnote`om izme|u napada oksidansa (one~i{}enja iz zraka) i antioksidacijskih procesa mo`e dovesti do o{te}enja plu}a i nastanka kroni~nih opstruktivnih bolesti plu}a (5). Kod prometnih policajaca u Indiji mjerenja su pokazala da izlo`enost prometu smanjuje razine antioksidansa poput katalaze, superoksid dismutaze i glutation peroksida.…”
Section: Klju^ne Rije^i: Fotokemijske Reakcije Oksidativni Stres Onunclassified
“…Reakcije [2], [3], [5] i [19] glavni su izvor OH radikala u troposferi. Reakcija [19] obi~no te~e na vi{im nadmorskim visinama, u sredinama gdje je zbog niskog sadr`aja vodene pare ograni~ena reakcija [3].…”
Section: Klju^ne Rije^i: Fotokemijske Reakcije Oksidativni Stres Onunclassified